A method for detecting the coating life of a galvanized steel pipe

CN122595855APending Publication Date: 2026-08-18HANDAN YOU FA STEEL PIPE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611046933.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-08-18

AI Technical Summary

Technical Problem

[0003]本发明的目的在于提供一种镀锌钢管镀层寿命检测方法,旨在解决现有技术中对镀锌钢管镀层寿命检测误差较大的问题

Benefits of technology

[0014]The beneficial effects of the galvanized steel pipe coating life detection method provided by this invention are as follows: Compared with the prior art, the galvanized steel pipe coating life detection method of this invention conducts a layered corrosion test in step S1, decoupling the uniform dissolution behavior of the pure zinc layer from the passivation decay behavior of the iron-zinc alloy layer from the data source, thus solving the defect that traditional overall measurement cannot distinguish the corrosion process of the two layers; then, in step S2, a layered corrosion kinetic model is constructed, setting a power function decay form for the characteristic of the pure zinc layer being mainly uniform dissolution, and setting a decay form with decreasing corrosion rate for the characteristic of the iron-zinc alloy layer being controlled by the densification of the passivation film, and introducing a model switching mechanism, which not only faithfully depicts the real corrosion evolution law of the two layers, but also fundamentally eliminates the problem that the model is unsolvable due to the extremely dense passivation film of the iron-zinc alloy layer; finally, in step S3, the model is calibrated using the layered data and the graded life results are output. The present invention provides a method for detecting the coating life of galvanized steel pipes. It implements the principle of layered processing throughout the entire process, so that the life prediction results closely match the actual corrosion behavior of the galvanized layer. This effectively overcomes the principle prediction deviation caused by the overall modeling and significantly reduces the detection error of the coating life of galvanized steel pipes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122595855A_ABST
    Figure CN122595855A_ABST
Patent Text Reader

Abstract

This invention provides a method for detecting the coating life of galvanized steel pipes, belonging to the field of metal coating performance testing technology. The method includes the following steps: S1, a layered corrosion test to obtain the remaining thickness data of the pure zinc layer and the iron-zinc alloy layer at different corrosion stages; S2, constructing a layered corrosion kinetic model, using a power-law decay law for the pure zinc layer stage and a decay law reflecting the densification of the passivation film for the iron-zinc alloy layer stage, and setting a model switching mechanism; S3, calibrating the model based on the remaining thickness data to output the depletion life of the pure zinc layer and / or the red rust initiation life of the substrate. This invention provides a method for detecting the coating life of galvanized steel pipes, overcoming the fundamental prediction bias caused by holistic modeling and significantly reducing the detection error of the galvanized steel pipe coating life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal coating performance testing technology, and more specifically, relates to a method for testing the coating life of galvanized steel pipes. Background Technology

[0002] Hot-dip galvanized steel pipes consist of an outer pure zinc layer (η phase) and an inner iron-zinc alloy layer (ζ, δ, Γ phases). These two layers differ fundamentally in chemical composition, microstructure, and corrosion electrochemical behavior. Corrosion of the pure zinc layer is primarily uniform dissolution, resulting in white rust on the surface, mainly affecting initial appearance and protective performance. The iron-zinc alloy layer, with its high hardness and positive potential, experiences corrosion at a rate that decays over time due to the influence of its own corrosion products and passivation film. The depletion of this passivation film directly leads to the initiation of red rust in the substrate and protective failure. However, most existing coating life testing methods treat the coating as a homogeneous whole, using a single corrosion rate model for overall calculation, failing to distinguish the significant differences between the two stages in corrosion mechanism, rate evolution, and failure criteria. This holistic modeling fundamentally leads to a serious deviation between predicted life and actual conditions, especially for the iron-zinc alloy layer corrosion stage, where prediction errors are extremely large. Summary of the Invention

[0003] The purpose of this invention is to provide a method for detecting the coating life of galvanized steel pipes, aiming to solve the problem of large errors in the detection of the coating life of galvanized steel pipes in the prior art.

[0004] To achieve the above objectives, the technical solution adopted by the present invention is: to provide a method for detecting the coating life of galvanized steel pipes, comprising the following steps: S1. Conduct a layered corrosion test to obtain the remaining thickness data of the pure zinc layer and the iron-zinc alloy layer on the galvanized steel pipe under test at different corrosion stages. S2. Establish a corrosion kinetic model that includes a pure zinc layer corrosion stage and an iron-zinc alloy layer corrosion stage; wherein, the corrosion rate evolution law of the pure zinc layer stage is set as a power function decay form, and the corrosion rate evolution law of the iron-zinc alloy layer stage is set as a combination mechanism that first adopts an exponential decay form and automatically switches to a power law decay form when the exponential decay form cannot obtain an effective solution. S3. Based on the remaining thickness data obtained from the layered corrosion test, the corrosion kinetic model is calibrated to obtain the coating lifetime prediction model, and the coating lifetime results, including the depletion lifetime of the pure zinc layer and / or the initiation lifetime of the red rust in the substrate, are output.

[0005] In one possible implementation, step S1 includes a cyclic accelerated corrosion test and / or an on-site plate-mounted corrosion test. The cyclic accelerated corrosion test adopts a cyclic working condition of alternating salt spray wetting and constant temperature drying, and uses multi-frequency eddy current non-destructive testing technology to obtain the remaining thickness of the pure zinc layer and the iron-zinc alloy layer on the galvanized steel pipe to be tested. The on-site hanging test involves placing the sample at an atmospheric test site in the target service environment, taking samples periodically, and using multi-frequency eddy current non-destructive testing technology to obtain the remaining thickness of the pure zinc layer and the iron-zinc alloy layer on the galvanized steel pipe under test.

[0006] In one possible implementation, the multi-frequency eddy current nondestructive testing technology maps the impedance signals acquired at multiple excitation frequencies to the thicknesses of the pure zinc layer and the iron-zinc alloy layer through a pre-established inversion calibration model. The establishment of the inversion calibration model includes: using the correspondence between the multi-frequency impedance signals of the same material sample and the standard thickness of the metallographic section, a mapping function is constructed using a multivariate nonlinear regression or backpropagation neural network method.

[0007] In one possible implementation, the cyclic conditions of the cyclic accelerated corrosion test include: During the salt spray wetting stage, the temperature inside the chamber was 35±2℃, and a 5% NaCl solution was continuously sprayed for 4 hours. During the constant temperature drying stage, stop spraying, raise the temperature inside the chamber to 60±2℃, force ventilation to reduce the relative humidity to below 30%, and maintain this temperature for 4 hours. The salt spray wetting stage and the constant temperature drying stage are performed alternately, forming a complete corrosion cycle.

[0008] In one possible implementation, the multiple excitation frequencies include four frequency points: 100Hz, 1kHz, 10kHz, and 100kHz. During formal testing, a multi-frequency eddy current probe is used to perform a spiral scan along the sample surface to collect the impedance amplitude and phase signals at each frequency point. The impedance amplitude and phase signals are then input into the inversion calibration model to simultaneously obtain the remaining thickness of the pure zinc layer and the iron-zinc alloy layer.

[0009] In one possible implementation, in step S2, the power-law decay form of the pure zinc layer corrosion stage is expressed as: in, To corrode to The remaining thickness of the pure zinc layer at that time. The initial thickness of the pure zinc layer. The reaction rate constant of the pure zinc layer is... The corrosion product influence index is 0 < ≤1; when When the zinc layer drops below a preset depletion threshold, it is determined that the pure zinc layer is depleted, and the depletion time is recorded. .

[0010] In one possible implementation, in step S2, the attenuation form and model switching mechanism of the iron-zinc alloy layer corrosion stage are as follows: by As an independent corrosion time for the iron-zinc alloy layer, an exponential decay rate model is adopted: in, for The instantaneous corrosion rate of the iron-zinc alloy layer at any given time. The initial corrosion rate when the iron-zinc alloy layer is first exposed. Define the passivation attenuation coefficient; define the limiting depth. ; when > The depletion time of the iron-zinc alloy layer is calculated using the following formula. : when ≤ When the time comes, it automatically switches to the power-law decay residual thickness model: and according to The solution takes a very long time, where The corrosion constant of the iron-zinc alloy layer is... It is a time exponent and 0 < <1; The total lifetime of red rust initiation in the matrix was determined to be .

[0011] In one possible implementation, step S3 includes the calibration as follows: Using the time series of remaining delamination thicknesses of the pure zinc layer and the iron-zinc alloy layer at different corrosion stages obtained from the cyclic accelerated corrosion test, a nonlinear least squares fitting method was used to determine the reaction rate constant of the pure zinc layer corrosion stage in the corrosion kinetic model. And the influence index of corrosion products And the initial corrosion rate of the iron-zinc alloy layer corrosion stage. and passivation attenuation coefficient .

[0012] In one possible implementation, step S3 further includes: Using the remaining thickness data of the pure zinc layer and the iron-zinc alloy layer obtained from the field plating test under real-world conditions, the average consumption rate of the pure zinc layer under real-world conditions was extracted. The average corrosion rate of the iron-zinc alloy layer under real-world conditions ; The average consumption rate of pure zinc layer at the corresponding stage was extracted from the data of the cyclic accelerated corrosion test. and the average corrosion rate of the iron-zinc alloy layer ; Define the conversion acceleration coefficient of pure zinc layer The conversion coefficient of the iron-zinc alloy layer ; The reaction rate constant K1 is corrected to The initial corrosion rate is corrected to The and It remains unchanged.

[0013] In one possible implementation, step S3, the calibration further includes introducing an initial coating uniformity correction factor. The according to Calculate, where, The circumferential thickness uniformity coefficient, is the axial thickness uniformity coefficient. and These are the minimum and average thicknesses in the circumferential direction, respectively. and These are the minimum axial thickness and the average thickness, respectively. The depletion lifetime of the pure zinc layer and the rust initiation lifetime of the substrate, predicted based on the average thickness, are multiplied by [percentage missing]. This yields the lifespan corresponding to the weakest area of ​​the coating.

[0014] The beneficial effects of the galvanized steel pipe coating life detection method provided by this invention are as follows: Compared with the prior art, the galvanized steel pipe coating life detection method of this invention conducts a layered corrosion test in step S1, decoupling the uniform dissolution behavior of the pure zinc layer from the passivation decay behavior of the iron-zinc alloy layer from the data source, thus solving the defect that traditional overall measurement cannot distinguish the corrosion process of the two layers; then, in step S2, a layered corrosion kinetic model is constructed, setting a power function decay form for the characteristic of the pure zinc layer being mainly uniform dissolution, and setting a decay form with decreasing corrosion rate for the characteristic of the iron-zinc alloy layer being controlled by the densification of the passivation film, and introducing a model switching mechanism, which not only faithfully depicts the real corrosion evolution law of the two layers, but also fundamentally eliminates the problem that the model is unsolvable due to the extremely dense passivation film of the iron-zinc alloy layer; finally, in step S3, the model is calibrated using the layered data and the graded life results are output. The present invention provides a method for detecting the coating life of galvanized steel pipes. It implements the principle of layered processing throughout the entire process, so that the life prediction results closely match the actual corrosion behavior of the galvanized layer. This effectively overcomes the principle prediction deviation caused by the overall modeling and significantly reduces the detection error of the coating life of galvanized steel pipes. Attached Figure Description

[0015] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0016] Figure 1 This is a flowchart illustrating a method for detecting the coating life of galvanized steel pipes, as provided in an embodiment of the present invention. Detailed Implementation

[0017] To make the technical problems to be solved, the technical solutions, and the beneficial effects of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the present invention and are not intended to limit the present invention.

[0018] Please see Figure 1This invention provides a method for detecting the coating life of galvanized steel pipes, comprising the following steps: S1, conducting a layered corrosion test to obtain the remaining thickness data of the pure zinc layer and the iron-zinc alloy layer on the galvanized steel pipe under test at different corrosion stages; S2, constructing a corrosion kinetic model including the pure zinc layer corrosion stage and the iron-zinc alloy layer corrosion stage; wherein, the corrosion rate evolution law of the pure zinc layer stage is set to a power function decay form, and the corrosion rate evolution law of the iron-zinc alloy layer stage is set to a combination mechanism that preferentially adopts an exponential decay form and automatically switches to a power law decay form when the exponential decay form cannot obtain an effective solution, so as to ensure that a finite exhaustion time is obtained; S3, calibrating the corrosion kinetic model based on the remaining thickness data obtained from the layered corrosion test to obtain a coating life prediction model, and outputting the coating life result including the pure zinc layer exhaustion life and / or the substrate red rust initiation life.

[0019] This method stems from a profound understanding of the shortcomings of existing technologies: hot-dip galvanized coatings are not homogeneous structures, but rather a two-layer system composed of an outer pure zinc layer (η phase) and an inner iron-zinc alloy layer (ζ, δ, Γ phases). These two layers differ fundamentally in chemical composition, microstructure, electrochemical potential, and corrosion evolution. Existing detection methods treat the coating as a homogeneous whole, using a single corrosion rate model for overall calculation. This fundamentally leads to a significant deviation between the predicted lifespan and actual conditions, especially for the iron-zinc alloy layer corrosion stage, where the prediction error is extremely large. To fundamentally solve this problem, this invention implements a layered processing principle throughout the entire process from experimental design and model construction to data calibration, ensuring that the detection results closely match the actual corrosion behavior of the galvanized layer.

[0020] In step S1, the stratified corrosion test includes a cyclic accelerated corrosion test and / or an on-site plate-mounted corrosion test.

[0021] The core of step S1 in this invention lies in decoupling the corrosion behaviors of the two layers from the data source. Existing technologies typically only measure changes in the total coating thickness or the overall weight loss of the sample; these macroscopic data cannot distinguish the individual corrosion processes of the pure zinc layer and the iron-zinc alloy layer. However, the pure zinc layer is primarily characterized by anodic dissolution, resulting in a relatively uniform corrosion rate; the iron-zinc alloy layer, due to the gradual densification of the passivation film from corrosion products, exhibits a significantly reduced corrosion rate over time. If the data from both layers are combined for modeling, a compromise single rate must be used for fitting, and regardless of the rate value, it cannot accurately describe the true behavior of both layers simultaneously. Therefore, obtaining data layer by layer is a fundamental prerequisite for subsequent layered modeling and accurate prediction.

[0022] The cyclic accelerated corrosion test employs alternating cycles of salt spray wetting and constant temperature drying, and utilizes multi-frequency eddy current non-destructive testing technology to obtain the remaining thickness of the pure zinc layer and the iron-zinc alloy layer.

[0023] The reason for choosing cyclic operation conditions instead of traditional continuous neutral salt spray is that, under continuous salt spray conditions, the sample surface is always covered by a liquid film and remains in a constantly wet state. The dissolution products of the pure zinc layer cannot undergo the temporary protective layer formed by dehydration during the drying process, and the passivation behavior of the corrosion products of the iron-zinc alloy layer is also significantly altered under permanent wet conditions. This leads to a systematic deviation between the corrosion mechanism of the accelerated test and the real atmospheric alternating wet and dry environment. Cyclic operation conditions, by alternately introducing wetting and drying stages, simulate the natural rain-evaporation cycle, making the corrosion mechanism of the accelerated test closer to the real atmosphere, thus ensuring the reliability and accuracy of the subsequent accelerated-real conversion relationship.

[0024] The cyclic accelerated corrosion test operates under the following conditions: During the salt spray wetting stage, the chamber temperature is 35±2℃, and a 5% NaCl solution is continuously sprayed for 4 hours; during the constant temperature drying stage, spraying is stopped, the chamber temperature is raised to 60±2℃, and forced ventilation is used to reduce the relative humidity to below 30%, maintaining this for 4 hours. These two stages are repeated alternately to form a complete corrosion cycle. The parameters were determined based on extensive literature review and preliminary experiments: 35℃ is a suitable temperature for accelerating zinc corrosion, providing sufficient acceleration without triggering abnormal phase transitions in the corrosion products (e.g., the rate of Zn(OH)2 dehydration to ZnO changes drastically at excessively high temperatures); 5% NaCl solution is an internationally accepted standard salt spray medium; and a drying temperature of 60℃ allows for rapid evaporation of the surface liquid film to restore the sample to a dry state, while remaining below the glass transition temperature of the epoxy sealing material, ensuring that the sealing layer will not soften or de-adhere during long-term testing. The beneficial effects of this cyclic operating condition are that, compared to continuous salt spray, it makes the corrosion process of the accelerated test more closely resemble the alternation of dry and wet conditions in the real atmosphere in terms of mechanism. From the perspective of test design, it reduces the systematic bias of subsequent conversions and is the first line of defense to ensure the accuracy of the final life prediction.

[0025] In accelerated corrosion testing, a key technical challenge is how to continuously obtain the layer thicknesses of pure zinc and iron-zinc alloy layers without damaging the sample. Traditional methods require periodically removing parallel samples to create metallographic sections and then observing and measuring the thickness of each layer under a microscope. This method is highly destructive, produces discrete data, and struggles to capture transition points. To overcome these shortcomings, this invention employs multi-frequency eddy current testing technology as a non-destructive testing method. Its physical principle is as follows: when a coil probe carrying alternating current approaches a conductive metal surface, it excites eddy currents in the metal surface. The distribution range and penetration depth of these eddy currents are closely related to the frequency of the excitation current. The relationship between the penetration depth δ and the frequency f is as follows: Where μ is the magnetic permeability of the material and σ is the electrical conductivity. Therefore, using a lower excitation frequency can achieve a deeper penetration depth and detect deeper material information; using a higher excitation frequency will concentrate the eddy currents near the surface, making it more sensitive to changes in surface properties.

[0026] Due to the significant differences in chemical composition and microstructure between the pure zinc layer and the iron-zinc alloy layer, their electrical conductivity σ and magnetic permeability μ exhibit identifiable differences. The pure zinc layer is non-ferromagnetic or weakly magnetic; the iron-zinc alloy layer, due to its higher iron content, exhibits a certain degree of ferromagnetism, and its electrical conductivity and magnetic permeability differ from those of the pure zinc layer. When a multi-frequency eddy current probe is used to excite the same detection location sequentially at multiple frequencies, the eddy current distribution range and intensity at different frequencies are influenced by the combined effects of the thickness of each layer and its electromagnetic properties. Therefore, the impedance amplitude and phase signals picked up by the probe contain layering information from the surface layer to the substrate. The multiple excitation frequencies include at least four frequency points: 100Hz, 1kHz, 10kHz, and 100kHz. During formal testing, the multi-frequency eddy current probe is used to perform a spiral scan along the sample surface, acquiring the impedance amplitude and phase signals at each frequency point. These impedance amplitude and phase signals are then input into the inversion calibration model to simultaneously obtain the remaining thickness of the pure zinc layer and the iron-zinc alloy layer.

[0027] The multi-frequency eddy current nondestructive testing technology maps impedance signals acquired at multiple excitation frequencies to the thicknesses of the pure zinc layer and the iron-zinc alloy layer using a pre-established inversion calibration model. The establishment of the inversion calibration model includes: utilizing the correspondence between the multi-frequency impedance signals of samples of the same material and the standard thickness of the metallographic cross-section, and constructing a mapping function using multivariate nonlinear regression or backpropagation neural network methods. In application, the process of establishing the inversion calibration model is as follows: A batch of galvanized steel pipes of the same material, specifications, and process as those used in the formal test are taken. Signals are first acquired at different locations on their surface using a multi-frequency eddy current system with the same parameters as the formal test, recording the impedance amplitude and phase at each frequency. Then, a cross-section is immediately cut at the test location, and a cross-sectional metallographic sample is prepared using a standard metallographic procedure. The thicknesses of the pure zinc layer and the iron-zinc alloy layer are accurately measured under a microscope and used as standard values. After accumulating a sufficient number of calibration data pairs, mathematical methods such as multivariate nonlinear regression or backpropagation neural networks are used to establish a mapping function from the multi-frequency impedance eigenvectors to the thicknesses of the pure zinc layer and the iron-zinc alloy layer. This mapping function constitutes the inversion calibration model. After cross-validation confirms that the prediction accuracy meets the requirements, it can be used in formal experiments. By performing multi-frequency eddy current scanning on the sample and inputting the collected impedance signal into this calibration model, the remaining thicknesses of the pure zinc layer and the iron-zinc alloy layer can be obtained without damaging the sample.

[0028] The advantages of using multi-frequency eddy current nondestructive testing technology are: the same sample can be continuously tracked and tested throughout the entire corrosion cycle to obtain continuous dynamic change data of layer thickness; it avoids the data dispersion introduced by individual differences of different samples in traditional metallographic methods, thus improving the model fitting accuracy; and it significantly saves the preparation cost and labor cost of parallel samples.

[0029] The field-mounted sample test involves placing the specimen at an atmospheric test site within the target service environment. After periodic sampling, multi-frequency eddy current nondestructive testing (MDT) is used to determine the remaining thickness of the pure zinc layer and the iron-zinc alloy layer. While accelerated corrosion testing can rapidly obtain full-cycle data, it is essentially a simulation and intensification of the real environment, inevitably introducing a certain degree of environmental bias. The field-mounted sample test directly exposes the specimen to the target service environment, where the corrosion process occurs under the combined effects of real temperature, humidity, pollutant concentration, sunlight, and rainfall conditions, eliminating any distortions introduced by accelerated simulation. Therefore, the field-mounted sample data serves as an irreplaceable calibration benchmark for subsequent model calibration.

[0030] The specific implementation method of the on-site hanging plate test is as follows: Representative atmospheric environment test sites are selected, covering different corrosion levels from rural clean areas to coastal salt spray areas. The samples are fixed at an angle consistent with the service posture of steel pipes in actual engineering (e.g., 45° angle) to ensure that rainwater and condensation can flow away smoothly without forming liquid accumulation. The hanging plate bracket is made of the same substrate as the sample and has undergone the same hot-dip galvanizing process. All contact points between the sample and the bracket are equipped with insulating gaskets made of polytetrafluoroethylene or nylon to completely eliminate galvanic corrosion caused by contact between dissimilar metals. Multiple parallel samples are placed at each type of environmental site, and samples are taken periodically according to a preset time cycle. After each sampling, the samples are immediately sent back to the laboratory, and parameter testing is performed according to the same multi-frequency eddy current delamination thickness detection procedure as for accelerated test samples. Delamination corrosion data, such as the remaining thickness of the pure zinc layer and the remaining thickness of the iron-zinc alloy layer, are obtained under real-world conditions and at different corrosion stages.

[0031] The field-based data and accelerated testing data complement each other: the accelerated testing data provides high-temporal-resolution dynamic information on the entire corrosion process, used to establish the kinetic equation structure of the model and preliminarily calibrate parameters; the field-based data provides steady-state corrosion rate information under real-world conditions, used to convert and calibrate the accelerated testing parameters to real-world conditions. The combination of these two data sources ensures both the accuracy of the model's description of the corrosion mechanism and a high degree of consistency between the model's predictions and the actual service environment.

[0032] Regarding sample preparation and pretreatment, to ensure the reliability of test data, it is necessary to eliminate galvanic corrosion and edge liquid accumulation effects caused by exposed substrate at the sample end faces. Specifically: tubular samples are cut from the galvanized steel pipe to be tested using a water-cooled cutting machine to avoid melting or phase transformation of the coating near the cut due to thermal cutting; the sample surface is cleaned with anhydrous ethanol to remove oil and dust; an inert sealing material (such as two-component epoxy resin) is used to completely cover the cut end faces of the sample. Before the sealing material cures, a forming scraper with a specific bevel angle is used to rotate and scrape along the circumference of the pipe, forming a smooth transition section with a slope of no more than 30° between the sealing material and the coating surface. After curing, the integrity of the seal is checked. When the slope of the transition section is less than 30°, the liquid film cannot remain stably and will flow away smoothly under gravity, thus effectively eliminating local accelerated corrosion caused by edge liquid accumulation. This pretreatment measure can reduce the interference of end face galvanic corrosion and edge effects on the test results to a very low level.

[0033] In step S2, a corrosion kinetic model is established that includes a pure zinc layer corrosion stage and an iron-zinc alloy layer corrosion stage. The corrosion rate evolution law for the pure zinc layer stage is set to a power-law decay form, while the corrosion rate evolution law for the iron-zinc alloy layer stage is set to a combined mechanism that preferentially uses an exponential decay form and automatically switches to a power-law decay form when the exponential decay form cannot obtain an effective solution, to ensure a finite exhaustion time. Independent corrosion rate evolution laws are set for the two stages based on their respective corrosion mechanisms.

[0034] Step S2 is the core step of this invention. The coating of hot-dip galvanized steel pipe exhibits a distinct double-layer characteristic in its microstructure. The outer layer is an η-phase pure zinc layer, with a zinc content typically above 99%, and its microstructure consists of coarse columnar or equiaxed crystals with high chemical activity. In a corrosive environment, the pure zinc layer mainly undergoes an anodic dissolution reaction: Zn → Zn 2+ + 2e - The dissolved zinc ions react with OH- in the environment. - CO2, Cl - The reaction produces white corrosion products such as basic zinc carbonate, zinc oxide, or zinc hydroxychloride, commonly known as "white rust." These white rust products have a loose structure and high porosity, which only slightly hinders the transport of corrosive media (water, oxygen, chloride ions, etc.) to the surface of the pure zinc layer. Therefore, the corrosion of the pure zinc layer is mainly a uniform dissolution proportional to the contact area with the corrosive media, and the corrosion rate is approximately constant, with only a slight slowing trend as the white rust coating gradually thickens.

[0035] For the pure zinc layer corrosion stage, the power function decay form is expressed as: in, To corrode to The remaining thickness of the pure zinc layer at time (unit: μm). The initial thickness of the pure zinc layer (unit: μm). The reaction rate constant of the pure zinc layer is... Corrosion time (unit: h). The corrosion product influence index has a value range of 0 < ≤1.

[0036] when When = 1, the equation degenerates into a linear decay, corresponding to an ideal homogeneous dissolution scenario without the hindering effect of white rust products. In actual corrosion processes, The value, slightly less than 1, typically between 0.85 and 0.95, reflects the slight physical effect of the white rust coating in hindering the corrosive medium. This power function form flexibly characterizes the continuous behavior from purely linear to slightly hindered, perfectly matching the physicochemical properties of pure zinc layers, which are primarily characterized by uniform dissolution with slight product inhibition. When the calculated... When the zinc layer drops below a preset depletion threshold (e.g., 0.5 μm), it is considered depleted, and this moment is recorded as _____. The depletion of the pure zinc layer signifies the loss of its protective function; the corresponding lifespan is known as the "pure zinc layer depletion lifespan."

[0037] After the pure zinc layer is depleted, the underlying iron-zinc alloy layer is directly exposed to the corrosive environment. This layer consists of multiple intermetallic compounds, including ζ, δ, and Γ phases, with the iron content gradually increasing from the outermost to the innermost layers. Each sublayer exhibits different electrochemical potentials, hardness, and corrosion behaviors. The corrosion of the iron-zinc alloy layer is primarily electrochemical. Its corrosion products (such as iron-containing zinc oxide and basic zinc ferric chloride) differ significantly in structure and properties from the white rust of the pure zinc layer. The corrosion products of the iron-zinc alloy layer are more dense. As corrosion progresses, these dense products gradually accumulate on the surface, forming a continuous passivation film that effectively inhibits the further diffusion of corrosive media (especially oxygen and chloride ions) into the iron-zinc alloy layer. Therefore, the corrosion rate of the iron-zinc alloy layer is not constant but continuously decreases as the passivation film thickens and densifies, exhibiting a typical "self-inhibition" kinetic characteristic.

[0038] For the corrosion stage of the iron-zinc alloy layer, the specific combination mechanism is as follows: For the independent corrosion time of the iron-zinc alloy layer, the exponential decay rate model is preferred: in, for The instantaneous corrosion rate of the iron-zinc alloy layer at any given time. The initial corrosion rate is given when the iron-zinc alloy layer is first exposed, representing the maximum corrosion activity before the passivation film has formed. The passivation attenuation coefficient characterizes the rate at which the passivation film forms and inhibits corrosion; the limiting depth is defined. ; As can be seen from this formula, the cumulative consumption depth asymptotically approaches the limit value. .when > The depletion time of the iron-zinc alloy layer is calculated using the following formula. : Received As a finite positive value, the total lifetime for the initiation of red rust on the matrix is... .

[0039] However, in some corrosive environments, the passivation film of the iron-zinc alloy layer is extremely dense, leading to a limiting depth that can be fitted. It may be less than or equal to the initial thickness of the iron-zinc alloy layer. At this point, the above equation has no real solutions mathematically, meaning the exponential decay model cannot consume the entire iron-zinc alloy layer within a finite time, which contradicts the fact that red rust inevitably occurs in engineering practice. To resolve this contradiction, this invention further establishes a model completeness judgment and switching mechanism: when the exponential decay model is used to fit the limit depth obtained from the experimental data... > When the time comes, it automatically switches to the power-law decay residual thickness model: and according to Solving takes a long time. The corrosion constant of the iron-zinc alloy layer is... It is a time exponent and 0 < <1; The total lifetime of matrix red rust initiation was determined to be .

[0040] This model has no limit to the thickness consumed, and the function will inevitably cross zero within a finite time, thus ensuring a reasonable finite depletion lifetime for the iron-zinc alloy layer. The above combined mechanism prioritizes the exponential decay rate model, which better reflects the dominant mechanism of passivation film-controlled corrosion. When the exponential decay model cannot consume the entire iron-zinc alloy layer within a finite time due to the extremely dense passivation film, it automatically switches to the power-law remaining thickness model. This ensures both faithfulness to the dominant mechanism of iron-zinc alloy layer passivation film-controlled corrosion and applicability to all scenarios, as well as the self-consistency of the model logic, fundamentally eliminating the risk of the model being unsolvable.

[0041] In step S3, the corrosion kinetic model is calibrated based on the remaining thickness data obtained from the layered corrosion test to obtain a coating lifetime prediction model, which is used to output coating lifetime results including the depletion lifetime of the pure zinc layer and / or the initiation lifetime of red rust in the substrate.

[0042] First, using the time series of remaining delamination thickness of the pure zinc layer and the iron-zinc alloy layer at different corrosion stages obtained from the cyclic accelerated corrosion test, a nonlinear least squares fitting method was employed to determine the reaction rate constant of the pure zinc layer corrosion stage in the corrosion kinetic model. And the influence index of corrosion products And the initial corrosion rate of the iron-zinc alloy layer corrosion stage. and passivation attenuation coefficient .

[0043] Secondly, using the remaining thickness data of the pure zinc layer and the iron-zinc alloy layer obtained from the on-site hanging test under real-world conditions, the average consumption rate of the pure zinc layer under real-world conditions was extracted. The average corrosion rate of the iron-zinc alloy layer under real-world conditions The average consumption rate of pure zinc layer at the corresponding stage was extracted from the data of the cyclic accelerated corrosion test. and the average corrosion rate of the iron-zinc alloy layer Define the conversion acceleration coefficient of the pure zinc layer. The conversion coefficient of the iron-zinc alloy layer The reaction rate constant K1 was corrected to... The initial corrosion rate is corrected to The and It remains unchanged.

[0044] It is important to emphasize that, due to the drastically different chemical compositions, electrochemical potentials, and corrosion mechanisms of pure zinc layers and iron-zinc alloy layers, their sensitivity to accelerated corrosion environments differs. The anodic dissolution reaction of pure zinc layers is extremely sensitive to chloride ion concentration and humidity, and its corrosion amplification factor is typically high in accelerated salt spray environments. In contrast, the corrosion of iron-zinc alloy layers is controlled by the passivation film, which may be damaged by high concentrations of chloride ions in accelerated environments, weakening its protective effect. Therefore, its acceleration factor is not entirely consistent with that of pure zinc layers. Usually greater than This is precisely the fundamental reason why existing technologies using a single overall conversion coefficient inevitably introduce systematic errors. This invention employs layered calibration, calculating the corrected real-world environmental dynamic parameters separately.

[0045] Furthermore, the calibration also includes introducing a correction factor for the initial uniformity of the coating. The according to Calculate, where, The circumferential thickness uniformity coefficient, is the axial thickness uniformity coefficient. and These are the minimum and average thicknesses in the circumferential direction, respectively. and These are the minimum axial thickness and the average thickness, respectively; the depletion lifetime of the pure zinc layer and the red rust initiation lifetime of the substrate, predicted based on the average thickness, are multiplied by [missing information]. This yields the lifespan corresponding to the weakest area of ​​the coating.

[0046] In actual production, hot-dip galvanized steel pipes are affected by fluctuations in the galvanizing process parameters, resulting in a certain degree of non-uniformity in the coating thickness both circumferentially and axially. During corrosion service, the thinnest area of ​​the coating will be the first to be corroded through, becoming the failure starting point for the entire steel pipe. If the model only calculates based on the average thickness, the predicted "average life" will be based on the average thickness, leading to a risky assessment result. Therefore, a correction factor for initial coating uniformity is introduced. This allows the prediction results to better reflect the actual situation where the coating fails first in engineering practice.

[0047] Furthermore, environmental correction coefficients can be introduced during the calibration process to enhance the model's automatic adaptability to different service environments. Due to significant differences in key parameters such as humidity, corrosive medium concentration, and temperature fluctuations in different atmospheric environments, corrosion rates can vary by several times or even tens of times. Repeating the entire on-site loading and accelerated testing calibration process for each target environment would be extremely costly. Therefore, this invention achieves environmental adaptive correction through a pre-established environmental factor library. The factor library is constructed by classifying the atmospheric environment into several levels of corrosivity according to international standards such as ISO 9223, and establishing dose-response functions for key parameters such as humidity, corrosive medium concentration, and temperature fluctuations.

[0048] Humidity Influence Sub-factor It can be expressed in the form of an exponential function: ,in This refers to the annual average relative humidity or the percentage of annual wet time in the target environment. This is a reference humidity value (e.g., 60%). Humidity sensitivity coefficient. Chloride ion deposition rate sub-factor: sulfur dioxide deposition rate factor ,in , For reference only. , This is the concentration index, typically taken as 0.4–0.8. Temperature fluctuation factor. ,in The typical diurnal or annual temperature range of the target environment. This represents the temperature fluctuation sensitivity coefficient. The empirical constants in the dose-response function above (such as a, b1, b2, c, and various reference values) can be obtained by consulting the recommended values ​​in ISO 9223 and related atmospheric corrosion manuals, or by regression calibration using data from a small number of representative sites. The final environmental correction factor... It is the product of the sub-factors.

[0049] When using the model, simply input macroscopic environmental parameters such as the annual average temperature, annual average relative humidity, chloride ion deposition rate, and SO2 deposition rate of the target environment, and the model will automatically calculate the corresponding environmental correction coefficients. These coefficients can then be used to adjust the kinetic parameters to obtain the prediction results for that specific environment.

[0050] After all the above calibration and correction steps, the final output coating life result includes two levels: pure zinc layer depletion life and substrate red rust initiation life. These two levels correspond to different failure criteria and engineering significance: pure zinc layer depletion life corresponds to the time point when white rust completely covers the coating surface, serving as a failure indicator for the appearance protection function; substrate red rust initiation life corresponds to the time point when the coating is completely consumed, the steel substrate is exposed, and red rust begins to form, serving as a failure indicator for the structural protection function. By providing graded life output, users can select the corresponding life index according to the specific needs of their application scenarios, providing a more comprehensive and accurate decision-making basis for formulating inspection and maintenance strategies.

[0051] To make the technical solution, technical effects, and advantages over the prior art clearer and more specific, the following description is provided through embodiments and comparative examples. It should be understood that the data in the embodiments are used to illustrate the present invention and are not intended to limit the scope of protection of the present invention.

[0052] Example 1 This embodiment uses a batch of DN50 hot-dip galvanized welded steel pipes as the testing object. The steel pipe base material is Q235B low-carbon steel, produced using a conventional hot-dip galvanizing process. The designed average total coating thickness is 85μm, of which the average thickness of the pure zinc layer (η phase) is approximately 55μm, and the average thickness of the iron-zinc alloy layer is approximately 30μm. The target service environment is the atmospheric environment of a typical city in North China, with an average annual temperature of 12.5℃, an average annual relative humidity of 65%, and a chloride ion deposition rate of approximately 3.2mg / (m³). 2 ·d), SO2 deposition rate is approximately 25 mg / (m³). 2 ·d), which belongs to level C3 in the ISO 9223 standard.

[0053] Step S1 (Layer Corrosion Test): Twenty tubular samples, each 150 mm in length, were cut from the same batch of galvanized steel pipes using a water-cooled cutting machine. All samples were cleaned with anhydrous ethanol, and both ends were sealed with two-component epoxy resin, with a smooth transition section created using a 30° bevel scraper. The samples were randomly divided into two groups. The first group of 12 samples underwent a cyclic accelerated corrosion test, alternating between salt spray wetting (35±2℃, 5% NaCl solution spray for 4 hours) and constant temperature drying (60±2℃, RH<30%, 4 hours). All samples were removed after every four cycles, and a multi-frequency eddy current detection system was used to perform spiral scanning at four frequencies: 100 Hz, 1 kHz, 10 kHz, and 100 kHz. The impedance signal was input into a pre-calibrated inversion model to simultaneously obtain the remaining thickness of the pure zinc layer and the remaining thickness of the iron-zinc alloy layer. The test continued until the remaining thickness of the iron-zinc alloy layer fell below the detection limit, lasting approximately 45 days. The second group of 8 pieces were placed at the atmospheric environment test station in the target city for on-site hanging tests. They were installed at a 45° angle with nylon gaskets at the contact points. Two pieces were retrieved each time after 6, 12, 18, and 24 months of exposure, and the layer thickness was tested according to the same procedure.

[0054] Step S2 (Constructing a corrosion kinetic model): Using the time-series data of layer thickness obtained from accelerated testing, the kinetic parameters are fitted using the nonlinear least squares method. The pure zinc layer stage is modeled using a power-law decay function. , fitting , =0.93. The exponential decay model is preferentially used for the iron-zinc alloy layer stage. , fitting =0.24μm / h, =0.0085h -1 Calculate the limiting depth =0.24 / 0.0085≈28.2μm. Because (28.2μm) is less than the initial thickness of the iron-zinc alloy layer. (30μm) Triggers the model switching mechanism, automatically switching to the power-law decay remaining thickness model. , fitting m=0.5.

[0055] Step S3 (Model Calibration and Lifetime Output): Extract the average corrosion rate for each stage from the field plating data. Average consumption rate of pure zinc layer. The average rate of independent corrosion of the iron-zinc alloy layer after the depletion of the pure zinc layer is approximately 2.1 μm / month. Approximately 1.3 μm / month. Average consumption rate of pure zinc layer in accelerated testing. The average corrosion rate of the iron-zinc alloy layer is approximately 285 μm / month. Approximately 112 μm / month. Calculate the accelerated conversion coefficient of the pure zinc layer. = 135.7, Accelerated Conversion Coefficient of Pure Zinc Layer = 86.2. The corrected real-world environmental dynamic parameters are: = , (Power-law model parameters are corrected according to the corresponding acceleration conversion coefficients), n1 remains unchanged. Initial uniformity is checked, and the circumferential uniformity coefficient is measured. = 0.91, axial uniformity coefficient = 0.96, uniformity correction factor η = 0.87. Using the calibrated model, the depletion lifetime of the pure zinc layer is approximately 2.9 years, which multiplied by η results in approximately 2.5 years; the total lifetime of red rust initiation in the substrate is approximately 10.3 years, which multiplied by η results in approximately 9.0 years.

[0056] Verification of effectiveness: Long-term tracking of a set of verification samples (3 pieces) retained at the target city environmental testing station showed that the average measured time for complete depletion of the pure zinc layer was approximately 2.8 years, while the predicted value of this invention was 2.5 years, with a relative error of approximately 10.7%; the average measured time for the first appearance of red rust spots on the substrate was approximately 9.7 years, while the predicted value of this invention was 9.0 years, with a relative error of approximately 7.2%. The prediction errors in both stages were controlled within an acceptable range for engineering applications, fully verifying the accuracy of the method of this invention.

[0057] Comparative Example 1 (Prior Art – Single Overall Rate Model) Using the same galvanized steel pipe and experimental data as in Example 1, but processed according to typical existing techniques: only the total coating thickness was recorded as a function of time, and a single linear corrosion rate model was used for regression to obtain a constant overall corrosion rate; the ratio of the overall average consumption rate to the overall average consumption rate under accelerated conditions was calculated using the data from the coated plates, resulting in a single acceleration conversion coefficient; the total lifetime was extrapolated after correction using this coefficient. The calculation showed that the single overall model predicted a substrate red rust initiation lifetime of approximately 5.6 years, which, compared to the measured value of 9.7 years, resulted in a prediction error as high as 42.3%, severely underestimating the actual lifetime. The root cause of the error lies in the fact that the linear model cannot describe the decay of the corrosion rate of the iron-zinc alloy layer, and the single conversion coefficient cannot adapt to two different acceleration rates. This comparative example intuitively demonstrates the serious defects of existing overall modeling and the significant advantages of the layered modeling and layered calibration of this invention.

[0058] Example 2 (Adaptability verification at different environmental levels) The same batch of galvanized steel pipe samples as in Example 1 were selected, and the field testing was extended to three sites with significantly different environments: Site A was a C5 environment in the southern coastal area, Site B was a C2 environment in a dry rural area in Northwest China, and Site C was a C4 environment in an acid rain industrial zone in Southwest China. Accelerated test data and kinetic equation parameters were obtained from the results of Example 1. Only the environmental parameters for each site needed to be input in step S3, and the environmental correction coefficients for each site were automatically calculated using the environmental factor library, eliminating the need to conduct a complete accelerated test for each site again. A comparison of the model prediction results and long-term measured results for each site showed: Site A predicted a lifetime of 3.2 years, while the measured lifetime was approximately 3.5 years, with an error of 8.6%; Site B predicted 18.5 years, while the estimated lifetime was approximately 19.3 years, with an error of 4.1%; Site C predicted 6.7 years, while the measured lifetime was approximately 6.1 years, with an error of 9.8%. The prediction errors for all three sites were controlled within 10%, demonstrating that the environmental factor library has good environmental adaptability and versatility.

[0059] Comparative Example 2 (without environmental adaptive calibration) In the A-site test of Example 2, if the C3 environmental model parameters from Example 1 were used directly for prediction without environmental adaptive calibration, the predicted lifetime was 9.0 years, which is 157% higher than the measured value of 3.5 years at A-site. This comparative example shows that ignoring environmental differences can lead to catastrophic prediction bias, thus demonstrating the necessity and importance of the environmental adaptive calibration process.

[0060] Example 3 (Verification of the necessity of initial uniformity correction) A batch of DN80 galvanized steel pipes with poor coating uniformity were selected for testing. The average total coating thickness was 90 μm, but the circumferential uniformity coefficient was low. The axial uniformity coefficient is only 0.70. The uniformity correction coefficient is 0.88, and the overall uniformity correction coefficient η = 0.616. The complete process is performed according to the method of this invention. Without uniformity correction, the predicted substrate red rust initiation life based on the average thickness is approximately 12.1 years; after correction, it is reduced to approximately 7.5 years. On-site tracking shows that the first appearance of red rust in the thinnest circumferential area of ​​the coating is approximately 7.1 years. The error of the corrected prediction is only 5.6%, while the error without correction is as high as 70.4%. This embodiment fully verifies the important significance of initial uniformity correction in improving engineering safety.

[0061] As can be seen from the above embodiments and comparative examples, the method of the present invention significantly reduces the comprehensive prediction error of galvanized steel pipe coating life detection from 30% to 70% of the traditional method to less than 10%, achieving outstanding technical results.

Claims

1. A method for detecting the coating life of galvanized steel pipes, characterized in that, Includes the following steps: S1. Conduct a layered corrosion test to obtain the remaining thickness data of the pure zinc layer and the iron-zinc alloy layer on the galvanized steel pipe under test at different corrosion stages. S2. Establish a corrosion kinetic model that includes a pure zinc layer corrosion stage and an iron-zinc alloy layer corrosion stage; wherein, the corrosion rate evolution law of the pure zinc layer stage is set as a power function decay form, and the corrosion rate evolution law of the iron-zinc alloy layer stage is set as a combination mechanism that first adopts an exponential decay form and automatically switches to a power law decay form when the exponential decay form cannot obtain an effective solution. S3. Based on the remaining thickness data obtained from the layered corrosion test, the corrosion kinetic model is calibrated to obtain the coating lifetime prediction model, and the coating lifetime results, including the depletion lifetime of the pure zinc layer and / or the initiation lifetime of the red rust in the substrate, are output.

2. The method for detecting the coating life of galvanized steel pipes as described in claim 1, characterized in that, In step S1, the stratified corrosion test includes a cyclic accelerated corrosion test and / or an on-site plate-mounted corrosion test; The cyclic accelerated corrosion test adopts a cyclic working condition of alternating salt spray wetting and constant temperature drying, and uses multi-frequency eddy current non-destructive testing technology to obtain the remaining thickness of the pure zinc layer and the iron-zinc alloy layer on the galvanized steel pipe to be tested. The on-site hanging test involves placing the sample at an atmospheric test site in the target service environment, taking samples periodically, and using multi-frequency eddy current non-destructive testing technology to obtain the remaining thickness of the pure zinc layer and the iron-zinc alloy layer on the galvanized steel pipe under test.

3. The method for detecting the coating life of galvanized steel pipes as described in claim 2, characterized in that, The multi-frequency eddy current non-destructive testing technology uses a pre-established inversion calibration model to map the impedance signals collected at multiple excitation frequencies to the thickness of the pure zinc layer and the iron-zinc alloy layer. The establishment of the inversion calibration model includes: using the correspondence between the multi-frequency impedance signal of the same material sample and the standard thickness of the metallographic section, and constructing a mapping function using multivariate nonlinear regression or backpropagation neural network methods.

4. The method for detecting the coating life of galvanized steel pipes as described in claim 2, characterized in that, The cyclic conditions of the cyclic accelerated corrosion test include: During the salt spray wetting stage, the temperature inside the chamber was 35±2℃, and a 5% NaCl solution was continuously sprayed for 4 hours. During the constant temperature drying stage, stop spraying, raise the temperature inside the chamber to 60±2℃, force ventilation to reduce the relative humidity to below 30%, and maintain this temperature for 4 hours. The salt spray wetting stage and the constant temperature drying stage are performed alternately, forming a complete corrosion cycle.

5. The method for detecting the coating life of galvanized steel pipes as described in claim 3, characterized in that, The multiple excitation frequencies include four frequency points: 100Hz, 1kHz, 10kHz, and 100kHz. During formal testing, a multi-frequency eddy current probe is used to perform a spiral scan along the sample surface to collect the impedance amplitude and phase signals at each frequency point. The impedance amplitude and phase signals are then input into the inversion calibration model to simultaneously obtain the remaining thickness of the pure zinc layer and the iron-zinc alloy layer.

6. The method for detecting the coating life of galvanized steel pipes as described in claim 1, characterized in that, In step S2, the power function decay form of the pure zinc layer corrosion stage is expressed as: in, To corrode to The remaining thickness of the pure zinc layer at that time. The initial thickness of the pure zinc layer. The reaction rate constant of the pure zinc layer is... The corrosion product influence index is 0 < ≤1; when When the zinc layer drops below a preset depletion threshold, it is determined that the pure zinc layer is depleted, and the depletion time is recorded. .

7. The method for detecting the coating life of galvanized steel pipes as described in claim 1, characterized in that, In step S2, the attenuation mode and model switching mechanism of the iron-zinc alloy layer corrosion stage are as follows: by As an independent corrosion time for the iron-zinc alloy layer, an exponential decay rate model is adopted: in, for The instantaneous corrosion rate of the iron-zinc alloy layer at any given time. The initial corrosion rate when the iron-zinc alloy layer is first exposed. Define the passivation attenuation coefficient; define the limiting depth. ; when > The depletion time of the iron-zinc alloy layer is calculated using the following formula. : when ≤ When the time comes, it automatically switches to the power-law decay residual thickness model: and according to The solution takes a very long time, where The corrosion constant of the iron-zinc alloy layer is... It is a time exponent and 0 < <1; The total lifetime of red rust initiation in the matrix was determined to be .

8. The method for detecting the coating life of galvanized steel pipes as described in claim 2, characterized in that, In step S3, the calibration includes: Using the time series of remaining delamination thicknesses of the pure zinc layer and the iron-zinc alloy layer at different corrosion stages obtained from the cyclic accelerated corrosion test, a nonlinear least squares fitting method was used to determine the reaction rate constant of the pure zinc layer corrosion stage in the corrosion kinetic model. And the influence index of corrosion products And the initial corrosion rate of the iron-zinc alloy layer corrosion stage. and passivation attenuation coefficient .

9. The method for detecting the coating life of galvanized steel pipes as described in claim 8, characterized in that, In step S3, the calibration further includes: Using the remaining thickness data of the pure zinc layer and the iron-zinc alloy layer obtained from the field plating test under real-world conditions, the average consumption rate of the pure zinc layer under real-world conditions was extracted. The average corrosion rate of the iron-zinc alloy layer under real-world conditions ; The average consumption rate of pure zinc layer at the corresponding stage was extracted from the data of the cyclic accelerated corrosion test. and the average corrosion rate of the iron-zinc alloy layer ; Define the conversion acceleration coefficient of pure zinc layer The conversion coefficient of the iron-zinc alloy layer ; The reaction rate constant K1 is corrected to The initial corrosion rate is corrected to The and It remains unchanged.

10. The method for detecting the coating life of galvanized steel pipes as described in claim 9, characterized in that, In step S3, the calibration further includes introducing an initial coating uniformity correction factor. , ,in, The circumferential thickness uniformity coefficient, is the axial thickness uniformity coefficient. and These are the minimum and average thicknesses in the circumferential direction, respectively. and These are the minimum axial thickness and the average thickness, respectively. The depletion lifetime of the pure zinc layer and the rust initiation lifetime of the substrate, predicted based on the average thickness, are multiplied by [percentage missing]. This yields the lifespan corresponding to the weakest area of ​​the coating.